Voluntary isometric contractions at maximal shortening as a new technique to achieve neuromuscular re-education in healthy subjects - Julio-Artemi Hernández-Trujillo; María-Dolores González-Rivera; Jorge M. González-Hernández (Journal of Exercise Science & Fitness)
Background: objectives: Neuromuscular re-education has focused on improving motor activities in patients with pathologies by retraining the nervous system. However, this has not yet been investigated in healthy individuals. Voluntary isometric contractions at maximal muscle shortening (VICAMS) is a new technique with the same objective. This study aimed to investigate the chronic effects of these techniques on range of motion, strength, and vertical jump. Methods: Sixty healthy, recreationally active participants (mean age: 46.4 ± 5.5), were randomly assigned to three groups (VICAMS, ballistic stretching, and control) who were trained for eight weeks. To assess chronic effects, active range of motion, maximal isometric strength, and countermovement jump height were determined before and after the intervention. Results: Main effects of time and time∗group interactions were found for all variables (p < 0.001). Between-group differences were observed in the VICAMS group after the intervention, with significantly higher flexibility and strength values compared to the other groups. Intra-group differences were observed in the VICAMS and ballistic groups, as the values for all variables increased from baseline. In the VICAMS group, increases were observed in both flexibility (19.15 %) and strength (47.63 %). Increases in flexibility (2.59 %) and strength (1.84 %) were also observed in the ballistic group. For jumping, intra-group differences showed that both the VICAMS (16.56 %) and ballistic (4.34 %) groups had improved values compared to baseline values. Conclusion: Our findings suggest that VICAMS is an effective, simple, and inexpensive alternative to conventional training methods for improving flexibility and strength in rehabilitation.